(untitled) (Marketing Journal, 2025)
The article examines modern marketing strategies employed by textile enterprises in Uzbekistan to enhance their competitiveness in domestic and international markets. Using the examples of FULL COTTON LLC and BETLIS TEKSTIL LLC, the study analyzes existing approaches to product promotion, including digital channels, pricing policies, product range expansion, and participation in international exhibitions. 79 Special attention is given to the role of corporate culture in the successful implementation of marketing strategies. The study identifies key trends and challenges hindering sustainable development and provides recommendations for strengthening brand posi tioning, diversifying sales channels, improving product quality, and leveraging internal organizational resources as a source of competitive advantage.